Case report: Febrile infection-related epilepsy syndrome in a 14-year-old girl with multiple organ failure and lethal outcome - Ruttkowski, Lars; Wallot, Ines; Korell, Marie; Daur, Elke; Seipelt, Peter; Leonhardt, Andreas; Weber, Stefanie; Mand, Nadine (Frontiers in Neuroscience, 2024)
We report a case of an otherwise healthy 14-year-old girl with febrile infection-related epilepsy syndrome (FIRES), multiple organ failure (MOF), and ultimately a lethal outcome. This is a rare case of FIRES with MOF and consecutive death. Only a few cases have been described in the literature. The adolescent girl was initially admitted to our pediatric emergency department with a first episode of generalized tonic–clonic seizures after a short history of fever a week before admission. Seizures progressed rapidly into refractory status epilepticus without any evidence of the underlying cause, and treatment subsequently had to be escalated to thiopental anesthesia. Since the initial diagnostics showed no promising leads, the rare syndrome of FIRES was suspected, representing a catastrophic epileptic encephalopathy linked to a prior benign febrile infection. Methylprednisolone, intravenous immunoglobulins, and a ketogenic diet were initiated. Respiratory, circulatory, kidney, and liver failure developed during treatment, requiring increasing intensive care. Multiple attempts to deescalate antiepileptic treatment resulted in recurrent status epilepticus. A cranial MRI on the 10th day of treatment revealed diffuse brain edema and no cerebral perfusion. The patient was declared dead on the 11th day of treatment. FIRES should be taken into account in previously healthy children with a new onset of difficult-to-treat seizures after a short febrile infection when no other cause is apparent. First-line treatment, besides seizure control, is the early initiation of immunomodulatory therapy and the start of a ketogenic diet. As treatment is difficult and MOF may develop, patients should be transferred to a specialized children’s hospital providing full intensive care.